Cyclone risk model and assessment for East Asian container ports - Jian, Wei (2021)
A cyclone risk model for container ports is developed with a holistic approach on assessing the physical vulnerability of port infrastructure and goods to withstand cyclone events. The risk evaluation considers the structural survivability of the operation components at berth fronts, storage areas and internal transport system within a typical container terminal when subjected to the impact of cyclone wind and storm surge. We present the potential cyclone risks and economic losses for the top 14 East Asian container ports for their respective 100-year return period cyclone wind and storm surge events. The results suggest that many of the container ports are potentially faced with high economic losses: on average, 0.05 billion USD and up to 0.4 billion USD if widespread flooding occurs. The ports located in the Great Pearl River Delta and Yangtze River Delta are subject to the highest risks from both wind and storm surge perils. The maximum 100-year return period loss for these two port clusters can reach up to USD 0.1–0.2 billion under cyclone wind impact and USD 1.0–2.0 billion under storm surge impact. This calls for more effective port planning for cyclone preparedness and emergency response by port authorities and operators.